Positive electrode material, battery, and power using device

CN122992009APending Publication Date: 2026-10-27BEIJING CHEHEJIA AUTOMOBILE TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610261442.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-03-04
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0005]本申请提供一种正极材料、电池和用电设备,以解决相关技术中正极活性材料因发生体积膨胀和收缩导致正极活性材料与固态电解质层之间产生微观间隙的问题

Benefits of technology

本申请实施例所提供的正极材料包括内核和第一包覆层,内核包括正极活性材料,第一包覆层设置于内核表面,第一包覆层包括聚合物固态电解质。在本申请中,将包括聚合物固态电解质的第一包覆层包覆于内核表面,该第一包覆层与内核表面形成紧密的软性接触,在电池充放电循环中,当正极活性材料因活性离子的反复嵌入与脱出而发生体积膨胀与收缩时,包覆于内核表面的第一包覆层凭借自身的弹性形变能力,能够吸收和分散正极活性材料的体积形变应力,从而降低正极材料整体体积变化幅度,进而减小正极材料与固态电解质层之间的固-固界面的微观间隙,提升电池的倍率和循环寿命。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The application provides a positive electrode material, a battery and a power utilization device, wherein the positive electrode material comprises a core and a first coating layer; the core comprises a positive electrode active material; the first coating layer is arranged on the surface of the core; the first coating layer comprises a polymer solid-state electrolyte; the first coating layer can constrain the volume change of the positive electrode active material in the core by virtue of the elastic deformation capacity of the first coating layer, so as to achieve the purpose of buffering and absorbing the volume deformation stress of the positive electrode active material, thereby reducing the volume change amplitude of the positive electrode material and reducing the micro gap of the solid-solid interface between the positive electrode material and the solid-state electrolyte layer, and the rate and cycle life of the battery are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of battery technology, and in particular to a cathode material, a battery, and an electrical device. Background Technology

[0002] Solid-state batteries consist of a positive electrode, a solid electrolyte layer, and a negative electrode layer stacked sequentially. The solid electrolyte layer serves to isolate the positive and negative electrodes and to transport active ions.

[0003] During the charging and discharging process of a solid-state battery, the positive electrode active material of the positive electrode undergoes a reaction of intercalation and deintercalation of active ions, thereby achieving the storage and release of electrical energy.

[0004] However, during the process of inserting and deinserting active ions, the positive electrode active material will expand and contract in volume, which will lead to microscopic gaps or poor contact at the solid-solid interface between the positive electrode and the solid electrolyte layer. This will hinder the efficient transport of active ions and cause uneven local current distribution, ultimately accelerating the decline of battery capacity and cycle life. Summary of the Invention

[0005] This application provides a cathode material, a battery, and an electrical device to solve the problem in related technologies where the expansion and contraction of the cathode active material causes microscopic gaps between the cathode active material and the solid electrolyte layer.

[0006] To solve the above problems, this application provides the following technical solution: This application proposes a positive electrode material, including a core and a first coating layer, wherein the core includes a positive electrode active material; the first coating layer is disposed on the surface of the core and includes a polymer solid electrolyte.

[0007] In some embodiments, the positive electrode material further includes a second coating layer disposed on the surface of the first coating layer, the second coating layer comprising a halide solid electrolyte.

[0008] In some embodiments, the polymer solid electrolyte accounts for 0.01% to 1% of the mass of the positive electrode material, and the positive electrode active material accounts for 99% to 99.99% of the mass.

[0009] In some embodiments, in the positive electrode material, the polymer solid electrolyte accounts for 0.01% to 1% by mass, the halide solid electrolyte accounts for 15% to 30% by mass, and the positive electrode active material accounts for 69% to 84.99% by mass.

[0010] In some embodiments, the polymer solid electrolyte comprises a polymer matrix and a lithium salt, wherein the polymer matrix comprises at least one of vinylidene fluoride, polyethylene oxide, polymethyl methacrylate, polyimide, and polyacrylonitrile, and the lithium salt comprises at least one of lithium tetrafluoroborate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, and lithium hexafluorophosphate and lithium perchlorate. And / or, the average particle size of the polymer solid electrolyte is 1~20µm.

[0011] In some embodiments, the positive electrode active material includes any one of lithium iron phosphate, lithium cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt manganese aluminum oxide, and lithium-rich manganese-based positive electrode active materials. And / or, the average particle size of the positive electrode active material is 1.5~12µm.

[0012] In some embodiments, the chemical formula of the halide solid electrolyte is Li x AB6, where A is Zr, Ta, Sc, Y, In or Y, B is Cl or Br, and x is 2 or 3; And / or, the average particle size of the halide solid electrolyte is 0.5~25µm.

[0013] And / or, the thickness of the first coating layer is 10~50nm.

[0014] This application also proposes a battery including a positive electrode sheet, the positive electrode sheet including a positive current collector and a positive active material layer disposed on at least one side of the positive current collector, the positive active material layer including the aforementioned positive electrode material. This application also proposes an electrical device including the aforementioned battery, wherein the battery serves as the power supply for the electrical device.

[0015] In some embodiments, the electrical equipment includes a vehicle.

[0016] Compared with related technologies, the embodiments of this application have the following advantages: The cathode material provided in this application includes a core and a first coating layer. The core includes a cathode active material, and the first coating layer is disposed on the surface of the core, comprising a polymer solid electrolyte. In this application, the first coating layer comprising the polymer solid electrolyte is coated on the surface of the core, forming a tight, soft contact with the core surface. During battery charge-discharge cycles, when the cathode active material undergoes volume expansion and contraction due to the repeated insertion and extraction of active ions, the first coating layer coated on the core surface, by virtue of its own elastic deformation capability, can absorb and disperse the volume deformation stress of the cathode active material, thereby reducing the overall volume change of the cathode material, and further reducing the microscopic gap at the solid-solid interface between the cathode material and the solid electrolyte layer, thus improving the battery's rate capability and cycle life. Detailed Implementation

[0017] To make the above-mentioned objectives, features and advantages of this application more apparent and understandable, the application will be further described in detail below with reference to specific embodiments.

[0018] A solid-state battery includes a positive electrode, a solid electrolyte layer, and a negative electrode stacked sequentially. The positive electrode includes a positive current collector and a positive active material layer disposed on at least one side of the positive current collector. During the charging and discharging process of the battery, the positive active material in the positive active material layer undergoes a reaction of intercalation and deintercalation of active ions to achieve the storage and release of electrical energy. The solid electrolyte layer is responsible for isolating the positive and negative electrodes and transporting active ions between the positive and negative electrodes.

[0019] When active ions are inserted into the lattice of the positive electrode active material, the volume of the positive electrode active material expands. When active ions are extracted from the lattice of the positive electrode active material, the lattice structure of the positive electrode active material contracts, resulting in a reduction in the volume of the positive electrode active material. Therefore, during repeated charge and discharge, the positive electrode active material will undergo repeated volume expansion and contraction, which can easily cause microscopic gaps or poor contact at the solid-solid interface between the positive electrode active material and the solid electrolyte layer. This will affect the transport of active ions at the solid-solid interface between the positive electrode active material and the solid electrolyte layer, and ultimately affect the battery rate and cycle life.

[0020] Furthermore, when the solid electrolyte layer includes a sulfide solid electrolyte, the poor chemical and electrochemical stability of the sulfide solid electrolyte leads to side reactions at the interface between the sulfide solid electrolyte and the positive electrode active material under high voltage operation. These side reactions typically include the oxidation of the sulfide solid electrolyte, generating high-resistivity products such as lithium-sulfur compounds or phosphorus-sulfur compounds, further worsening the electrochemical impedance of the solid-solid interface between the solid electrolyte layer and the positive electrode active material, thus reducing the battery's charge and discharge efficiency.

[0021] To address the above issues, this application provides a positive electrode material comprising a core and a first coating layer. The core comprises a positive electrode active material, and the first coating layer is disposed on the surface of the core, comprising a polymer solid electrolyte.

[0022] In this embodiment, a first coating layer including a polymer solid electrolyte is coated on the core surface. The first coating layer forms a tight soft contact with the core surface. During the battery charge-discharge cycle, when the positive electrode active material of the core expands and contracts in volume due to the repeated insertion and extraction of active ions, the first coating layer coated on the surface of the positive electrode active material can absorb and disperse the volume deformation stress of the positive electrode active material by virtue of its own elastic deformation capability, thereby reducing the overall volume change of the positive electrode material, and thus reducing the microscopic gap of the solid-solid interface between the positive electrode material and the solid electrolyte layer, thereby improving the battery rate and cycle life.

[0023] In some embodiments, the average particle size of the positive electrode active material is 1.5 to 12 µm. Positive electrode active materials with an average particle size within this range have relatively regular morphology and relatively dense surfaces, facilitating uniform dispersion of the positive electrode active material in the positive electrode active material layer. In some embodiments, the average particle size of the positive electrode active material is 1.5 µm, 3 µm, 5 µm, 7 µm, 9 µm, 10 µm, or 12 µm.

[0024] In some embodiments, the positive electrode active material includes any one of lithium iron phosphate, lithium cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt manganese aluminum oxide, and lithium-rich manganese-based positive electrode active materials. These positive electrode active materials have high energy density and good reversible cycle performance, which is beneficial for producing batteries with high energy density and long cycle life.

[0025] Among them, lithium iron phosphate does not contain precious metals (such as cobalt and nickel) in its production process, and its main raw materials are lithium hydroxide, ferrous sulfate, and ammonium dioxin, making the cost controllable; lithium cobalt oxide has a relatively simple production process and is easy to prepare. Lithium cobalt oxide has good cycle performance and is suitable for applications requiring high cycle life; lithium nickel cobalt manganese oxide is a cathode active material whose comprehensive performance is optimized by adjusting the ratio of nickel, cobalt, and manganese, which can well balance energy density, cycle life, and safety; the introduction of aluminum in lithium nickel cobalt manganese aluminum oxide mainly plays a role in stabilizing the crystal structure, which can improve the thermal stability and cycle life of the cathode active material while maintaining high energy density, effectively alleviating the problems of rapid cycle decay and relatively insufficient thermal stability of high nickel materials; lithium-rich manganese-based cathode active material is a type of layered material with ultra-high specific capacity potential. During the first charge, lithium ions and oxygen ions in the structure of lithium-rich manganese-based cathode active material will participate in charge compensation, thereby releasing a high reversible capacity.

[0026] In some embodiments, the average particle size of the polymer solid electrolyte is 1-20 µm. By controlling the average particle size of the polymer solid electrolyte to 1-20 µm, it is beneficial to form a continuous first coating layer with sufficient thickness on the core surface when coating the positive electrode active material. In some embodiments, the average particle size of the polymer solid electrolyte is 1 µm, 4 µm, 5 µm, 8 µm, 10 µm, 15 µm, 18 µm, or 20 µm.

[0027] In some embodiments, the polymer solid electrolyte accounts for 0.01% to 1% of the mass of the positive electrode material, and the positive electrode active material accounts for 99% to 99.99% of the mass. By mixing the polymer solid electrolyte with the positive electrode active material, a first coating layer is formed on the surface of the positive electrode active material. This first coating layer can ensure high ionic conductivity and avoid hindering the extraction / intercalation of active ions from the positive electrode active material. At the same time, the first coating layer also has good elasticity or flexibility, and can absorb and disperse the stress generated by the volume change of the positive electrode active material through its own deformation, thereby reducing the microscopic gap of the solid-solid interface between the positive electrode material and the solid electrolyte layer, and improving the rate performance and cycle life of the battery.

[0028] In some embodiments, the thickness of the first coating layer is 2-15 nm. Within this thickness range, the first coating layer ensures high ionic conductivity to prevent hindering the insertion / extraction of active ions. Simultaneously, within this thickness range, the first coating layer adheres to the surface of the positive electrode active material and possesses sufficient elastic deformation to absorb and disperse stress caused by volume changes in the positive electrode active material. In some embodiments, the thickness of the first coating layer is 2 nm, 5 nm, 8 nm, 10 nm, or 15 nm.

[0029] In some embodiments, the polymer solid electrolyte comprises a polymer matrix and a lithium salt. The flexible long chains of the polymer matrix can closely adhere to the core, buffering and absorbing the volume changes of the positive electrode active material in the core during charging and discharging. The lithium salt provides free lithium ions to achieve active ion conduction, thereby improving the battery's rate capability and cycle life. The polymer matrix includes at least one of vinylidene fluoride, polyethylene oxide, polymethyl methacrylate, polyimide, and polyacrylonitrile. The lithium salt includes at least one of lithium tetrafluoroborate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium hexafluorophosphate, and lithium perchlorate.

[0030] In some embodiments, the polymer solid electrolyte includes at least one of polyethylene oxide-lithium bis(trifluoromethanesulfonyl)imide (PEO-LiTFSI), polyacrylonitrile-lithium perchlorate (PAN-LiClO4), polymethyl methacrylate-lithium bis(trifluoromethanesulfonyl)imide (PMMA-LiTFSI), polyvinylidene fluoride-lithium hexafluorophosphate (PVDF-LiPF6), or polycarbonate-lithium bis(trifluoromethanesulfonyl)imide (PPC-LiTFSI).

[0031] In some embodiments, the cathode material further includes a second coating layer disposed on the surface of the first coating layer, and the first coating layer includes a halide solid electrolyte.

[0032] In this embodiment, the halide solid electrolyte has high ionic conductivity. By coating the surface of the first coating layer with a second coating layer containing the halide solid electrolyte, a more efficient ion conduction channel can be provided for the positive electrode active material to extract / inserte active ions into the core, which is beneficial to improving the ionic conductivity of the positive electrode material and thus improving the rate performance of the battery. At the same time, the halide solid electrolyte also has a wide chemical stability window and can remain stable under high voltage conditions. Therefore, in this embodiment, the second coating layer isolates the positive electrode active material in a high oxidation state under high voltage operating conditions from the solid electrolyte layer, especially the solid electrolyte layer including the sulfide solid electrolyte, to suppress the catalytic oxidation of the solid electrolyte layer, especially the chemically active sulfide solid electrolyte, by the positive electrode active material, thereby ensuring the electrochemical stability and low impedance of the solid-solid interface between the positive electrode material and the solid electrolyte layer during long-term cycling.

[0033] In some embodiments, the second coating layer includes a halide solid electrolyte. In the cathode material, the mass percentage of the polymer solid electrolyte is 0.01% to 1%, the mass percentage of the halide solid electrolyte is 15% to 30%, and the mass percentage of the cathode active material is 69% to 84.99%. Through this ratio, the halide solid electrolyte can form a second coating layer with suitable thickness, good isolation effect, and high ionic conductivity on the surface of the first coating layer.

[0034] The chemical formula of the halide solid electrolyte is Li xAB6, where A is Zr, Ta, Sc, Y, In, or Y, B is Cl or Br, and x is 2 or 3. This halide solid electrolyte exhibits high room-temperature ionic conductivity. A highly efficient ion conduction network is constructed on the surface of the first coating layer through a second coating layer, providing a low-resistance channel for the rapid insertion and extraction of active ions from the positive electrode active material, thus improving the battery's rate performance. Simultaneously, the halide solid electrolyte possesses a wide electrochemical stability window, effectively preventing direct contact between the positive electrode active material and the chemically reactive solid electrolyte. This suppresses interfacial side reactions, avoids the formation of high-resistance decomposition products (such as lithium-sulfur compounds or phosphorus-sulfur compounds), and ensures the structural stability and low impedance of the interface between the solid electrolyte layer and the positive electrode material.

[0035] In some embodiments, the halide solid electrolyte includes at least one of Li3YCl6, Li3YBr6, Li3InCl6, Li2ZrCl6, Li2ZrBr6, and Li3TaCl6.

[0036] In some embodiments, the average particle size of the halide solid electrolyte is 0.5~25µm. Halide solid electrolytes within this particle size range can effectively coat the surface of the first coating layer, which is beneficial for forming a more complete and continuous second coating layer, thereby achieving the purpose of isolating the positive electrode active material from the solid electrolyte layer. In some embodiments, the average particle size of the halide solid electrolyte is 0.5µm, 2µm, 5µm, 10µm, 15µm, 20µm, or 25µm.

[0037] In some embodiments, the second coating layer can block violent side reactions that may occur between the positive electrode active material and the solid electrolyte layer under high voltage operating conditions, thereby improving the chemical stability of the interface between the solid electrolyte layer and the positive electrode active material. At the same time, since the halide electrolyte itself has high ionic conductivity, it ensures that lithium ions can efficiently pass through the layer, avoiding a reduction in the ion conduction efficiency of the positive electrode material.

[0038] This application also provides a method for preparing a positive electrode material, including step 101: mixing the positive electrode active material with a polymer solid electrolyte to form a first coating layer on the surface of the positive electrode active material, thereby obtaining the positive electrode material.

[0039] In the preparation process, the polymer solid electrolyte is dissolved in a solvent to form a polymer solid electrolyte solution. The solvent can be any one of dimethylformamide (DMF), N-methylpyrrolidone (NMP), tetrahydrofuran (THF), acetone, and chloroform. Subsequently, the positive electrode active material is mixed evenly with the polymer solid electrolyte solution and stirred at 80-90°C for 3-5 hours. Then, the solvent is removed by rotary evaporation using a rotary evaporator, finally obtaining a positive electrode active material with a surface coated with polymer solid electrolyte. The positive electrode active material with a surface coated with polymer solid electrolyte is then subjected to heat treatment, specifically at a heating rate of 2-5°C / min to 250-300°C and annealed for 5-6 hours, so that the polymer matrix in the polymer solid electrolyte undergoes a cross-linking reaction, and an elastic first coating layer is formed on the surface of the positive electrode active material, thus obtaining the positive electrode material.

[0040] In some embodiments, another method for preparing a cathode material is also provided, comprising the following steps: Step 201: Mix the positive electrode active material with the polymer solid electrolyte to form a first coating layer on the surface of the positive electrode active material, thereby obtaining the first positive electrode material; Step 202: Mix the first positive electrode material with the halide solid-solid electrolyte to form a second coating layer on the surface of the first positive electrode material, thereby obtaining the positive electrode material.

[0041] In this embodiment, the first positive electrode material is obtained through step 201, which is the same as step 101 in the above embodiment. Step 202 is to continue coating the surface of the first positive electrode material to form a second coating layer. Specifically, the positive active material coated with the first coating layer (i.e., the first positive electrode material) is mixed with a halide solid electrolyte and ball-milled in a planetary ball mill at a speed of 400-800 rpm for 1-2 hours, so that the halide solid electrolyte adheres to or coats the surface of the first positive electrode material, thereby forming a second coating layer on the surface of the first positive electrode material, and finally obtaining the positive electrode material.

[0042] This application also provides a battery, which includes a positive electrode sheet, a positive current collector, and a positive active material layer disposed on at least one side of the positive current collector. The positive active material layer includes the positive electrode material described in the above embodiments. The structure and technical effects of the positive electrode material in this embodiment are the same as those in the above embodiments. To avoid repetition, they will not be described again here. For relevant details, please refer to the description of the positive electrode material embodiments.

[0043] In some embodiments, the positive current collector may be aluminum foil or aluminum alloy foil, and the positive active material layer further includes a conductive agent and a binder. The conductive agent may include at least one of conductive carbon black, acetylene black, Ketjen black, carbon nanotubes, graphene, hard carbon, carbon fiber, and carbon microspheres; the binder may include at least one of polyvinylidene fluoride, polytetrafluoroethylene, vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, and tetrafluoroethylene-hexafluoropropylene copolymer.

[0044] In some embodiments, the positive electrode sheet is prepared as follows: the positive electrode material, binder and conductive agent are dispersed in a solvent such as N-methylpyrrolidone to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode current collector; after drying, a positive electrode active material layer is formed on the positive electrode current collector; and after further cold pressing, cutting, slitting and other processes, the positive electrode sheet can be obtained.

[0045] In some embodiments, the battery further includes a negative electrode sheet, which includes a negative current collector and a negative active material layer disposed on the negative current collector. The negative active material layer includes a negative active material, which includes any one or a combination of at least two of hard carbon, soft carbon, graphite, silicon carbon, silicon-based negative active material, lithium titanate, and lithium metal.

[0046] The negative electrode active material layer also includes a conductive agent and a binder; the conductive agent includes one or more of conductive carbon black, acetylene black, Ketjen black, carbon nanotubes, and graphene; the binder includes carboxymethyl cellulose-based binders and resin-based binders.

[0047] In some embodiments, when the battery is a solid-state battery, the battery further includes a solid electrolyte layer, which may be made of at least one of sulfide solid electrolyte, polymer solid electrolyte, oxide solid electrolyte and halide solid electrolyte.

[0048] Among them, oxide solid electrolytes, such as Li 6.4 La3Zr 1.4 Ta 0.6 O 12LLZTO (Lithium Sulfide Solid Electrolytes) possesses superior chemical and electrochemical stability and is highly stable in air, making it easy to process. Sulfide solid electrolytes, such as Li3PS4, are relatively simple to prepare, using simple solid-phase reactions or liquid-phase methods, and exhibit high room-temperature ionic conductivity. Halogen solid electrolytes, such as Li3YCl6, Li3YBr6, Li3InCl6, Li2ZrCl6, Li2ZrBr6, or Li3TaCl6, optimize the transport pathway of active ions, thus achieving high room-temperature ionic conductivity. Polymer solid electrolytes consist of a polymer matrix and a lithium salt. The flexible polymer chains tightly adhere to the electrode active material particles, buffering volume changes during charge and discharge, while the lithium salt provides free active ions for ion conduction, thereby improving battery cycle life.

[0049] In the process of preparing solid-state batteries, the positive electrode, solid electrolyte layer, and negative electrode can be stacked in sequence in a solid-state battery mold and then cured to obtain a solid-state battery.

[0050] In some embodiments, when the battery is a liquid battery, the battery further includes an electrolyte and a separator disposed between the positive electrode and the negative electrode. The electrolyte wets the surfaces of the positive electrode, the separator, and the negative electrode, and includes an electrolyte salt and a solvent. When the positive electrode active material layer of the positive electrode includes a positive electrode material, the first coating layer in the positive electrode material can buffer and absorb the stress caused by the volume change of the positive electrode active material in the core due to the intercalation / deintercalation reaction, which helps to ensure the structural integrity of the positive electrode active material in the core and prevent its cracking and failure. At the same time, the second coating layer can prevent the positive electrode active material in the core from directly contacting the electrolyte, ensuring the chemical stability of the positive electrode active material, thereby providing the cycle life and rate performance of the liquid battery.

[0051] In some embodiments, the electrolyte salt is a lithium salt, including at least one of lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(pentafluoroethylsulfonyl)imide, lithium hexafluorophosphate, lithium hexafluoroarsenate, lithium hexafluoroaluminate, lithium tetrafluoroborate, lithium difluorooxalate borate, lithium dioxoylborate, lithium difluorophosphate, and lithium nitrate; the solvent includes cyclic ester solvents and chain ester solvents. In some embodiments, the cyclic ester solvent includes at least one of ethylene carbonate, propylene carbonate, butenyl carbonate, and fluoroethylene carbonate; the chain ester solvent includes at least one of dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, methyl propyl carbonate, and diphenyl carbonate. In some embodiments, the solvent includes ethylene carbonate, propylene carbonate, and methyl ethyl carbonate.

[0052] In some embodiments, an electrical device is also provided, including a battery, which serves as a power source for the electrical device. It should be noted that the battery disclosed in this embodiment has the same structure as the battery in the above embodiments, and its beneficial effects are similar. Therefore, it will not be repeated here; relevant details can be found in the description of the battery embodiments.

[0053] In some embodiments, the electrical equipment includes a vehicle, which may be, but is not limited to, an electric vehicle, a hybrid vehicle, a range-extended electric vehicle, a fuel cell vehicle, an electric motorcycle, and an electric bicycle.

[0054] In some embodiments, the electrical device may also include humanoid robots, mobile phones, tablets, laptops, electric toys, ships, spacecraft, etc. Electric toys may include stationary or mobile electric toys, such as game consoles, electric car toys, electric ship toys, and electric airplane toys, etc. Spacecraft may include airplanes, rockets, space shuttles, and spacecraft, etc.

[0055] To make the inventive objectives, technical solutions, and beneficial effects of this application clearer, the present application is further described below with reference to embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of this application. Unless otherwise specified, the reagents and instruments used in the embodiments and comparative examples are all commercially available, and the experimental operations are performed in accordance with the product instructions and standard experimental procedures.

[0056] Example 1 (1) Preparation of cathode materials Based on mass parts, 0.05 parts of polyethylene oxide-bis(trifluoromethanesulfonyl)imide lithium (PEO-LiTFSI) were dissolved in N-methylpyrrolidone (NMP) to prepare a polymer solid electrolyte solution; subsequently, 99.95 parts of the positive electrode active material LiNi were added. 0.8 Co 0.1 Mn 0.1 O2 is mixed evenly with the polymer solid electrolyte solution and stirred at 80°C for 5 hours. Then, the solvent is removed by rotary evaporation to obtain a positive electrode active material with a surface coated with polymer solid electrolyte. The positive electrode active material with a surface coated with polymer solid electrolyte is then subjected to heat treatment, specifically heated to 300°C at a heating rate of 3°C / min and annealed for 5 hours to finally obtain a positive electrode active material with a first coating layer on the surface, i.e., the positive electrode material.

[0057] (2) Preparation of positive electrode sheet A positive electrode material, conductive agent, and binder were mixed in a mass ratio of 98:1:1, and an appropriate amount of solvent was added to prepare a positive electrode slurry. The positive electrode slurry was then coated onto aluminum foil to obtain an areal capacity of 5 mAh·cm³. -2The positive electrode sheet is prepared and dried in an oven at 100℃ for later use.

[0058] (3) Preparation of negative electrode sheet A 10mm thick lithium-indium alloy is deposited on the surface of copper foil to serve as the negative electrode.

[0059] (4) Preparation of solid electrolyte layer Li6PS5Cl powder was placed in a mold and a pressure of 100 MPa was applied to obtain a solid electrolyte layer with a thickness of 10 mm.

[0060] (5) Preparation of solid-state batteries In a glove box filled with argon (H2O < 1 ppm, O2 < 1 ppm), the positive electrode, solid electrolyte layer, and negative electrode are stacked and assembled in that order to obtain an electrode assembly. The electrode assembly is then placed in a lamination mold and subjected to isostatic pressing. During isostatic pressing, a pressure of 100 MPa is applied to the electrode assembly, and the isostatic pressing time is 30 minutes, thus obtaining a solid-state battery.

[0061] Example 2 The difference between Example 2 and Example 1 is that step (1) of Example 1 is adjusted as follows: Step (11) Preparation of the first cathode material Based on mass parts, 0.05 parts of polyethylene oxide-bis(trifluoromethanesulfonyl)imide lithium (PEO-LiTFSI) were dissolved in N-methylpyrrolidone (NMP) to prepare a polymer solid electrolyte solution; subsequently, 77.95 parts of the positive electrode active material LiNi were added. 0.8 Co 0.1 Mn 0.1 O2 is mixed evenly with the polymer solid electrolyte solution and stirred at 80°C for 5 hours. Then, the solvent is removed by rotary evaporation to obtain a positive electrode active material with a polymer solid electrolyte coating on its surface. The positive electrode active material with a polymer solid electrolyte coating on its surface is then subjected to heat treatment, specifically by heating to 300°C at a heating rate of 3°C / min and annealing for 5 hours to finally obtain a positive electrode active material with a first coating layer on its surface, which is also known as the first positive electrode material.

[0062] Step (12) Preparation of cathode material By mass fraction, the first cathode material from step (11) is mixed with 22 parts of halide solid electrolyte Li2ZrCl6 and ball-milled at 500 rpm for 1 hour in a planetary ball mill to form a second coating layer on the surface of the first cathode material, and finally the cathode material is obtained.

[0063] Examples 3-6 The difference between Examples 3-6 and Example 2 is that the polymer solid electrolyte in step (11) and the halide solid electrolyte in step (12) were adjusted.

[0064] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that step (1) is not performed, and in step (2), the positive electrode active material LiNi is... 0.8 Co 0.1 Mn 0.1 O2, conductive agent, and binder are mixed in a mass ratio of 98:1:1, and an appropriate amount of solvent is added to prepare a positive electrode slurry. The positive electrode slurry is then coated onto aluminum foil to obtain an areal capacity of 5 mAh·cm³. -2 The positive electrode sheet is prepared and dried in an oven at 100℃ for later use.

[0065] The relevant parameters for the solid-state batteries prepared in the above embodiments and comparative examples are shown in Table 1.

[0066] Table 1

[0067] The electrochemical performance of the solid-state batteries prepared in the above embodiments and comparative examples was tested using the following methods: (1) Initial discharge specific capacity test: The constant current charge and discharge was performed at 0.1C in the voltage range of 2.8~4.3V at a temperature of 25 ℃. The initial charge and discharge specific capacity and initial coulombic efficiency at 0.1C were measured. The test results are shown in Table 2. (2) Cyclic performance test: At a temperature of 25 ℃, constant current charge and discharge was performed at 0.33C within the voltage range of 2.8~4.3V. The first charge and discharge specific capacity at 0.33C was measured. The discharge capacity was measured as C1 after one cycle of constant current charge and discharge at 0.33C, and the discharge capacity was measured as C2 after 200 cycles of constant current charge and discharge at 0.33C. The capacity retention rate after 200 cycles at 0.33C was calculated as C2 / C1×100%. The test results are shown in Table 2.

[0068] Table 2

[0069] As can be seen from the results in Table 2, the initial discharge capacity, rate performance, and cycle performance of Examples 1-6 are comprehensively superior to those of the comparative examples, indicating that the first and second coating layers improve the interfacial and bulk stability of the positive electrode active material. Specifically, the first coating layer, with its flexibility, effectively buffers and absorbs the volume change stress of the positive electrode active material in the core during the lithium insertion / extraction process; while the second coating layer, with its high ionic conductivity and good chemical stability, not only reduces interfacial impedance and improves lithium-ion migration efficiency, but also suppresses side reactions between the positive electrode active material and the solid electrolyte layer under high voltage, thereby achieving the goal of improving the rate performance and cycle life of the battery.

[0070] Although preferred embodiments of the present application have been described, those skilled in the art, upon learning the basic inventive concept, can make other changes and modifications to these embodiments. Therefore, the claims are intended to be interpreted as including the preferred embodiments as well as all changes and modifications falling within the scope of the embodiments of the present application.

[0071] The above provides a detailed description of a positive electrode material, battery, and electrical device provided in this application. Specific examples have been used to illustrate the principles and implementation methods of this application. The descriptions of the above embodiments are only for the purpose of helping to understand the method and core ideas of this application. At the same time, for those skilled in the art, there will be changes in the specific implementation methods and application scope based on the ideas of this application. Therefore, the content of this specification should not be construed as a limitation of this application.

Claims

1. A positive electrode material, characterized in that, include: Core, the core comprising a positive electrode active material; A first coating layer is disposed on the surface of the core, and the first coating layer includes a polymer solid electrolyte.

2. The cathode material according to claim 1, characterized in that, The cathode material also includes: A second coating layer is disposed on the surface of the first coating layer, and the second coating layer includes a halide solid electrolyte.

3. The cathode material according to claim 1, characterized in that, In the cathode material, the polymer solid electrolyte accounts for 0.01% to 1% by mass, and the cathode active material accounts for 99% to 99.99% by mass.

4. The cathode material according to claim 2, characterized in that, In the cathode material, the polymer solid electrolyte accounts for 0.01% to 1% by mass, the halide solid electrolyte accounts for 15% to 30% by mass, and the cathode active material accounts for 69% to 84.99% by mass.

5. The cathode material according to any one of claims 1 to 4, characterized in that, The polymer solid electrolyte comprises a polymer matrix and a lithium salt. The polymer matrix comprises at least one of vinylidene fluoride, polyethylene oxide, polymethyl methacrylate, polyimide, and polyacrylonitrile. The lithium salt comprises at least one of lithium tetrafluoroborate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, and lithium hexafluorophosphate and lithium perchlorate. And / or, the average particle size of the polymer solid electrolyte is 1~20µm.

6. The cathode material according to any one of claims 1 to 5, characterized in that, The positive electrode active material includes any one of lithium iron phosphate, lithium cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt manganese aluminum oxide, and lithium-rich manganese-based positive electrode active materials. And / or, the average particle size of the positive electrode active material is 1.5~12µm.

7. The cathode material according to claim 2 or 4, characterized in that, The chemical formula of the halide solid electrolyte is Li x AB6, where A is Zr, Ta, Sc, Y, In or Y, B is Cl or Br, and x is 2 or 3; And / or, the average particle size of the halide solid electrolyte is 0.5~25µm; And / or, the thickness of the first coating layer is 2~15nm.

8. A battery, characterized in that, The positive electrode includes a positive current collector and a positive active material layer disposed on at least one side of the positive current collector, wherein the positive active material layer includes the positive electrode material as described in any one of claims 1 to 7.

9. An electrical appliance, characterized in that, Includes the battery as described in claim 8, wherein the battery serves as the power supply for the electrical device.

10. The electrical equipment according to claim 9, characterized in that, The electrical equipment includes vehicles.